Penguatan Kapasitas Orang Tua dalam Pengasuhan Anak: Implementasi Hukum Keluarga Islam di Era Digital di Kabupaten Sidenreng Rappang - Ahdiatul Badirah; Rusdaya Basri; Aris Aris; Rahmawati Rahmawati; Saidah Saidah (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This article discusses the strengthening of parental capacity in child parenting as an implementation of Islamic family law in the digital era in Sidenreng Rappang Regency. The study focuses on three issues: the reality of parenting in the digital era, supporting and inhibiting factors in the implementation of Islamic family law in parenting, and a model for strengthening parental capacity that is relevant to Islamic family law and contemporary digital life. This field research applies phenomenological and normative approaches. Primary data were obtained through in-depth interviews and observation of Muslim families in Sidenreng Rappang Regency, while secondary data were collected from books, journals, laws and regulations, the Compilation of Islamic Law, and other relevant sources. The data were analyzed qualitatively through data reduction, data display, and conclusion drawing using Baumrind’s parenting styles theory, digital literacy theory, and maqāṣid al-syarī‘ah theory. The findings show that digital-era parenting practices vary into authoritative, authoritarian, and permissive patterns. The authoritative pattern is considered the most relevant because it balances affection, communication, rules, supervision, and religious habituation. The supporting factors include the use of devices for school and communication, time limits, content monitoring, and religious values as the basis of supervision. The inhibiting factors include low parental digital literacy, inconsistent family rules, entertainment-dominated content, children’s resistance, secretive gadget use, and peer influence. The proposed model is Islamic digital parenting based on maqāṣid al-syarī‘ah through the protection of religion, life, intellect, lineage, and property.